2003
DOI: 10.1163/156854003771997864
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and population dynamics of the temperate freshwater shrimp, Neocaridina denticulata denticulata (De Haan, 1844), in a Korean stream

Abstract: Seasonal changes in population structure, reproductive activity, and growth of the shrimp Neocaridina denticulata denticulata were examined in a Korean stream between July 1999 and June 2001. Average population density ranged from 34 to 180 indiv. m ¡2 ; density declined during the rainy season as the population dispersed into freshly inundated areas. The main breeding season, from June to July, coincided with higher gonadosomatic indices. Within this season ovaries rematured during embryonic development, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Comparisons between the life history of N. davidi in the Tomoe River and that of N. denticulata as reported in previous studies (Ogawa et al, 1987;Niwa and Hamano, 1990;Sato et al, 1994;Oh et al, 2003) are presented in Table 1. Overall, the life history of N. davidi in the present study is quite similar to that of N. denticulata reported in previous studies.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Comparisons between the life history of N. davidi in the Tomoe River and that of N. denticulata as reported in previous studies (Ogawa et al, 1987;Niwa and Hamano, 1990;Sato et al, 1994;Oh et al, 2003) are presented in Table 1. Overall, the life history of N. davidi in the present study is quite similar to that of N. denticulata reported in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Both Neocaridina denticulata and N. davidi inhabited rivers mid-stream, lakes, marshes, and irrigation canals where emergent plants were abundant (Kamita, 1970;Ogawa et al, 1987;Sato et al, 1994;Suzuki & Sato, 1994;Englund & Cai, 1999;Oh et al, 2003;Liang, 2004;Hayashi, 2007;Suzuki & Naruse, 2011;Toyota & Seki, 2014). This sympatry potentially leads to competition between the two species for habitat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, during the breeding period, females that carry eggs cannot moult and therefore growth is inhibited (Oh et al 2003). Nevertheless, the growth of both males and females of P. macrodactylus was seasonal, started in September and finished in April, in accordance with the reproductive season.…”
Section: Discussionmentioning
confidence: 99%
“…Stations where no shrimp were caught were excluded from the comparison. The growth of the shrimp in this period was considered to be negligible, because several previous studies have shown that atyid shrimp show low or no growth at low temperatures (approximately 10°C; see, for example, Oh et al 2003, Yamahira et al 2007. A Wilcoxon Mann-Whitney rank sum test was used for data analyses using R version 2.14.1 (R Development Core Team 2011) and coin package for R (Hothorn et al 2006).…”
Section: Data Analysesmentioning
confidence: 99%